The perspectives of an electrical method of liquid parameters measurement in the frames of environment control - Матиборський, В. В.; Смирнитська, М. Б. (Proceedings of National Aviation University (archive), 2003)
In the article is spoken that the organs realizing ecological monitoring, feel necessity of gears for a measurement of parameters of liquids. The possibility of a solution of this problem with the help of devices, realizing an electrical method of a measurement of parameters of a liquid analyzed